Market Access for Developing Countries Exports - International Monetary Fund; World Bank (Washington, DC, 2014)
Integration into the world economy has proven a powerful instrument for countries to promote economic growth, development, and poverty reduction. Trade has been an engine of growth for the past fifty years, owing in part to eight successive rounds of multilateral trade liberalization, as well as unilateral and regional trade liberalization. The growing integration of the world economy has raised living standards and brought increased opportunity to many parts of the globe. Many developing countries have shared in this prosperity. As a group, developing countries have become much more important in world trade, and their trade relationships have changed markedly from the traditional north-south pattern. Developing countries now account for one-third of world trade, up from about a quarter in the early 1970s, and many have substantially increased their exports of manufactures and services relative to traditional commodity exports. The share of manufactures in developing country exports has risen to 80 percent; moreover, trade between developing countries has grown rapidly, with 40 percent of their exports now going to other developing countries.